Parental religiosity, parenting style and social responsibility among Muslim adolescents in Banda Aceh, Indonesia - Afriani, . (2011)
The linkages between religiosity with family process and child's outcomes have begun to be of interest to social scientists in recent years. Yet few have focused on these relationships, in particular between parental religiosity, parenting style and social adjustment among adolescents in Asian Muslim families. To address this paucity, the present study was primarily conducted to determine the contributions of parental religiosity and parenting style on social responsibility amongst Muslim adolescents residing in Banda Aceh, Indonesia. Additionally, the study determined if parenting style mediates the relationship between parental religiosity and adolescent social responsibility. A total of 331 adolescents aged between 11 to 18 years from two-parent families and from four high schools in two districts (Kuta Alam and Syiah Kuala) of Banda Aceh was identified using Multi-Stage Cluster sampling. Data were collected using self-administered questionnaire. Measurement for parental religiosity developed in this study was based on the dimensions of Islamic religiosity suggested by Azimi et al. (2006). Parental Authority Questionnaire (Buri, 1991) and Social and Personal Responsibility Scale (Conrad & Hedin, 1981) were used to assess parenting style and adolescent social responsibility, respectively. Findings from Pearson Product-Moment Correlation analyses showed parental religiosity to be positively related to perceived authoritarian (r mother=.25,p<.01; r father=.29,p<.01) and permissive parenting styles (r mother& r father=.19,p<.01), and adolescent social responsibility (rmother=.10,p<.05; rfather=.13,p<.01). In addition, the findings indicated that perceived parental authoritarian (r mother=.19,p<.01 and r father=.20,p<.01) and permissive styles (rmother=.36,p<.01 and rfather=.33, p<.01) to be significantly associated with improved adolescent social responsibility. On the other hand, a series of regression analyses indicated that parenting style (i.e. authoritarian and permissive) accounted for full mediation of the relationship between parental religiosity and adolescent social responsibility. Findings from this study suggest that parental religiosity plays a significant role in affecting adolescent social responsibility. Nevertheless, this association must be interpreted within the parenting context in which high parental religiosity potentially promotes two extreme ends of parenting behavior i.e. authoritarian and permissive parenting styles. The presence of these two parenting styles possibly affects adolescent social responsibility by overshadowing the significance of parental religiosity on adolescent social responsibility. The study thus, provides valuable information on how parents could enhance adolescent social responsibility through parental religiosity and parenting behavior. Findings from this study may have significant implications. Theoretically, the findings may shed light on the role of parental religiosity in influencing parental functioning and adolescent social behavior, particularly for Muslim families. From a practical perspective, the findings may imply that any effort in helping parents and their adolescents' development would be more effective when religion is taken into consideration.